Analisis Kualitas Pelayanan di Puskesmas Batang I Kabupaten Batang - Mujaddid Khoirunnas; Endang Larasati Setianingsih; Hardi Warsono (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
To support the achievement of health development, the government has provided some health facilities. One of the health facilities which was utilized by community is public health center. Public health center is Technical Implementation Unit of Health Department City/Regency which is responsible for the implementation of the health sector in the region. Public Health Center as the first implementation of basic facilities of public health are required to constantly improve professionalism in giving satisfaction to public. One of them is Puskesmas Batang 1 which is located in Batang sub-district of Batang regency. This study aimed to describe and analyze the quality of service and also the dimensions that obstruct and support those services. This study use descriptive qualitative method. The results showed that the quality of health center services is not good. This result seen from the five dimensions of Zeithaml. They are Tangibles, Reliability, Responsiveness, Assurance and Empathy. Because three of them as obstacle in dimension are Tangibles, Responsiveness and Assurance. In other hand, two of them are Reliability and Empathy be the dimension that supports the service. So it can be said that Batang 1 health center services have not comply the five dimensions of service according to Zeithaml.